Thyroid Hormone Withdrawal Further Exacerbates Oxidative Stress in Patients with Thyroid Carcinoma - Unluhizarci, K.; Kiris, A.; Kose, K.; Tanrikulu, E.; Karaca, Z.; Tanriverdi, F.; Kelestimur, F. (Experimental and Clinical Endocrinology & Diabetes, 2016)
Purpose: Hypothyroidism has profound effects on multiple organs and systems including cellular oxidative damage. Thus, we aimed to investigate the effects of acute hypothyroidism on oxidative stress in patients with differentiated thyroid carcinoma (DTC).Patients: 33 patients with DTC were involved in the study. 23 healthy subjects matched for age and body mass index (BMI) served as control group. Fasting blood sample was obtained for the determination of blood chemistry, lipids, myeloperoxidase (MPO) activity, total lipid hydroperoxide (LHP), pyrrolized protein, protein carbonyl compounds (PCC), advanced oxidation protein products (AOPP) and thiol levels before and after thyroid hormone withdrawal (THW) in patients with DTC.Results: MPO activity, total LHP, pyrrolized protein, PCC and AOPP levels were significantly higher, but thiol levels were significantly lower in patients with DTC while on L-thyroxine treatment than those of healthy subjects. At acute hypothyroid status after THW, MPO activity, total LHP, pyrrolized protein, PCC and AOPP levels further increased, thiol levels further decreased in patients with DTC as compared to healthy subjects and to their on L-thyroxine treatment period.Conclusions: This study showed an increased oxidative stress in patients with DTC which is further exacerbated with acute hypothyroidism upon THW. This situation may have treatment implications such as antioxidant therapy, at least during THW.
Keywords: thyroid hormone withdrawal; hypothyroidism; oxidative stress